Virgin forests of the European North-East - Vladimir Pakhuchiy (European Regional Science Association (ERSA), 2014)
The European North-East is one of the regions of Russia where have remained virgin forests. Firstly that is consequence of difference this territory from southern areas with higher degree of agricultural development. Cutting of forests for charcoal and fuel wood were fulfilled in small volumes. In spite of increase since 30th years of previous century in region volumes of the timber cuttings, all above mentioned are promoted for conservation here of large virgin forest massifs. The basic areas of the European North-East with virgin forests are located in the Komi Republic on the western slope of Ural Mountains, including in territories of National park 'Jugyd-Va', Pechoro-Ilychskiy reservation and its buffer zones. In 1995 those territories were included UNESCO in the List of the world cultural and natural heritage with name "Virgin forests Komi". The bulk of our researches were executed in Komsomolskiy forestry (lesnitchestvo) of Komi Republic. Virgin stands in the basin of river Unja basically concern to bilberry wet and fern forest type. Fir, spruce and sibirian cedar pine are the main trees of stands. Trees form the complex two-three-storied stands. The natural regeneration of the spruce and a fir domi-nate. The undergrowth of an average category of height (0,6-1,5 m) prevails. The average age of spruce is 159 - 199 years. The average growing stock is 170 - 180 m3ha-1. After analysis of definitions «virgin forest» which was done by other author and on the base of investigations we can give own conception for definitions «virgin forest massif» and «virgin stand». On the basis of the executed researches the offer is given at carrying out inventory works to consider incorporation possibility in a category of mountain forests of forests on western and parts of east slope of High Parma. It is recommended to distinguish water protective belts in borders of a catchment basin for a left-bank of upper parts of the Pechora river and for all extent of river Unja. Practical realization of these offers would promote conservation of virgin forests in southeast areas of the Komi Republic, differing by high productivity and rich species composition in comparison with northern and western territories of republic.
Keywords: 330; European North-East; Komi Republic; virgin forests; preservation of virgin forests